PENGARUH PEMBERIAN BOKASI TITONIA (Titonia diversifolia) PADA OXIC DYSTRUDEPTS LEMBAN TONGOA TERHADAP SERAPAN P DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU - Rara, Sely Limbong; Wahyudi, Imam; Widjajanto, Danang (AGROTEKBIS, 2013)
This study attempted to determine changes in Phosphorus (P)  uptake and the onion production by applying Titonia bokashi (Titonia diversifolia) in this oxic Dystrudepts  soil from Lemban Tongoa village from Palolo district, in pot experiment. The research was compiled in a Randomized Design (RBD) consists of 7 level of doses  of bokashi  namely control (without bokashi),  5 t ha-1,  10 t ha-1,  15 t ha-1 ,  25 t ha-1, 40 t ha-1, and 60 t ha-1, each treatment was repeated three times. Results showed that application of bokashi in oxic Dystrudepts significantly affect on changes in soil chemical properties, the Aldd reduced but available and total P, soil pH, plant dry weight, C-organic,  P uptake by onion increased.  Highest phosphorus (P) in onion (Allium ascalonicum L.) was found when Titonia bokashi  applied at a dose of 40 t ha-1.